2021
DOI: 10.1093/cid/ciab552
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Health Among People With Human Immunodeficiency Virus (HIV) Eligible for Primary Prevention: Insights From the REPRIEVE Trial

Abstract: Background In addition to traditional cardiovascular (CV) risk factors, antiretroviral therapy, lifestyle, and HIV-related factors may contribute to future CV events in persons with HIV (PWH). Methods Among participants in the global REPRIEVE randomized trial, we characterized demographics and HIV characteristics relative to ACC/AHA Pooled Cohort Equations (PCE) for atherosclerotic CV disease predicted risk and CV health eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Although factors unique to HIV, including persistent vascular inflammation and immune activation, play a role in increased CVD risk [24], traditional CVD risk factors are important as well [25,26]. These findings enrich our understanding of modifiable risk factors and highlight that diet quality, while not often assessed in CVD risk assessment, may be an important factor in the large global population of PWH as has been demonstrated in REPRIEVE [27]. Interestingly, total cholesterol and glucose did not demonstrate clinically meaningful changes across diet quality categories.…”
Section: Discussionmentioning
confidence: 83%
“…Although factors unique to HIV, including persistent vascular inflammation and immune activation, play a role in increased CVD risk [24], traditional CVD risk factors are important as well [25,26]. These findings enrich our understanding of modifiable risk factors and highlight that diet quality, while not often assessed in CVD risk assessment, may be an important factor in the large global population of PWH as has been demonstrated in REPRIEVE [27]. Interestingly, total cholesterol and glucose did not demonstrate clinically meaningful changes across diet quality categories.…”
Section: Discussionmentioning
confidence: 83%
“…By describing the temporal rise in CVD and its risk factors, we hope to encourage physicians to have increased vigilance for CVD and its associated risk factors among PLWH. Recent studies have shown only a limited percentage of PLWH achieving ideal cardiovascular health [ 43 ]. While smoking, alcohol use and substance use appear to be on the decline among VLHW, they should still sould be encouraged to work on lifestyle modifications, including but not limited to weight loss, exercise, and diet.…”
Section: Discussionmentioning
confidence: 99%
“…Undiagnosed and untreated hypothyroidism have significant public health and economic impacts, primarily due to the high costs that come with the complications of the disease [12]. Therefore, screening for hypothyroidism in older women and newborns, treatment, and prevention programs (universal salt iodization) is mandatory in many countries [10,12,17]. Moreover, screening for thyroid disease is beneficial because overt hypothyroidism has non-specific symptoms, and patients with SH are asymptomatic [10,15].…”
Section: Hypothyroidismmentioning
confidence: 99%